2003
DOI: 10.1016/s0163-7258(02)00328-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of glutamate dysregulation: implications for schizophrenia and its treatment

Abstract: The glutamate system is involved in many aspects of neuronal synaptic strength and function during development and throughout life. Synapse formation in early brain development, synapse maintenance, and synaptic plasticity are all influenced by the glutamate system. The number of neurons and the number of their connections are determined by the activity of the glutamate system and its receptors. Malfunctions of the glutamate system affect neuroplasticity and can cause neuronal toxicity. In schizophrenia, many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
165
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(186 citation statements)
references
References 352 publications
(394 reference statements)
11
165
0
7
Order By: Relevance
“…Ketamine-induced changes in mental status (Lahti et al, 1995b;Krystal et al, 1994) and brain metabolism (Vollenweider et al, 1997b;Holcomb et al, 2001;Breier et al, 1997;Lahti et al, 1995a) have been hypothesized to reflect antagonism of NMDARs located on inhibitory interneurons (probably GABAergic) in the anterior thalamus. That antagonism, in turn, may cause increased glutamate-dependent excitation in downstream cortical regions like the ACC (Farber, 2003;Newcomer et al, 1999;Krystal et al, 1994Krystal et al, , 2003Konradi and Heckers, 2003). In support of this idea, preclinical studies have revealed that NMDAR antagonism results in (1) increased frontal extracellular glutamate (Moghaddam et al, 1997;Lorrain et al, 2003;Takahata and Moghaddam, 2003) and acetylcholine levels (Giovannini et al, 1994), and (2) increased spontaneous firing rate of neurons in the frontal cortex (Moghaddam and Jackson, 2003;Homayoun et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine-induced changes in mental status (Lahti et al, 1995b;Krystal et al, 1994) and brain metabolism (Vollenweider et al, 1997b;Holcomb et al, 2001;Breier et al, 1997;Lahti et al, 1995a) have been hypothesized to reflect antagonism of NMDARs located on inhibitory interneurons (probably GABAergic) in the anterior thalamus. That antagonism, in turn, may cause increased glutamate-dependent excitation in downstream cortical regions like the ACC (Farber, 2003;Newcomer et al, 1999;Krystal et al, 1994Krystal et al, , 2003Konradi and Heckers, 2003). In support of this idea, preclinical studies have revealed that NMDAR antagonism results in (1) increased frontal extracellular glutamate (Moghaddam et al, 1997;Lorrain et al, 2003;Takahata and Moghaddam, 2003) and acetylcholine levels (Giovannini et al, 1994), and (2) increased spontaneous firing rate of neurons in the frontal cortex (Moghaddam and Jackson, 2003;Homayoun et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypofunction of the ionotropic glutamate NMDA receptor 75 and its modification 76 may play an important role in the pathophysiology and treatment of negative symptoms, respectively, and lead to inhibition of GABAergic interneurons. 77 GABA plays a key role in the function of the prefrontal cortex, an area impaired in schizophrenia 78 and linked to negative symptoms and cognitive impairment, 79,80 including working memory, a core cognitive deficit in the illness. 81 Antipsychotic drugs can modify GABA and glutamate system elements, including GABA A receptor, extracellular GABA levels and expression, glutamate transporters, 82 and neuregulin-1 (which regulates the expression of NMDA and GABA A receptors), 83 as well as ionotropic and metabotropic glutamate receptors.…”
Section: Clinical Relevancementioning
confidence: 99%
“…28 Given the low a priori odds that any gene will be a risk factor, the interpretation and validity of candidate gene results is critically dependent on existing information about the biology of the gene relative to the biology of the disease. Abnormal glutamatergic signaling has been a prominent 'hypothesis' about the pathophysiology of schizophrenia, 29,30 and it has been suggested that a number of the genes currently implicated in schizophrenia are related to NMDA (N-methyl-D-aspartate) signaling in the brain. [31][32][33] An equally prominent hypothesis involves gamma-aminobutyric acid (GABA) neuronal function, [34][35][36][37] but this avenue has been relatively unexplored from a genetic perspective.…”
Section: Introductionmentioning
confidence: 99%